RESULTS REGARDING PRIMULA OFFICINALIS HILL. TECHNOLOGY AND POSIBILITY FOR INTRODUCTION INTO CULTURE - Sorina NIȚU (NASTASE); Emilia CONSTANTINESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The oldest form of treatment, over time, was phytotherapy, which was probably born with human being. Popular medicine has developed on an empirical basis in the context of a magical world where analogy and coincidence have played an important role in choosing remedy plants. Regarding the multiple biological effects of Primula officinalis Hill., the scientific literature highlighted anti-asthmatic, anti-inflammatory and strong antiviral properties. Glycosides contained in this plant have a role in the treatment of kidney and biliary disorders, bronchitis and some gastrointestinal diseases. Primrose is an endangered plant in many Western European countries. In Romania, the plant is found in hills, pastures and alpine meadows up to about 2300-2400 m altitude. Research regarding introduction to culture are ongoing at National Institute of Research and Development for Potato and Sugar Beet Braşov. This paper presents the results obtained regarding the cultivation technology and the establishment of the possibility for introduction into culture. To establish these experiences, the plants were harvested from the spontaneous flora in 2016 and then acclimated to the greenhouses in the Technology Department, Laboratory of medicinal and aromatic plants. In the second experimental year, during the vegetation, observations and measurements were made in dynamics on each experimental variant to highlight the phenological stages regarding the formation of vegetative and generative organs in Primula officinalis (the emergence, the development of the foliar apparatus, the initiation of the floral buttons, the appearance of flowering stems, flowering, capsule and seed formation).